The Moral Psychology Handbook 2010
DOI: 10.1093/acprof:oso/9780199582143.003.0014
|View full text |Cite
|
Sign up to set email alerts
|

Race and Racial Cognition

Abstract: A core question of contemporary social morality concerns how we ought to handle racial categorization. By this we mean, for instance, classifying or thinking of a person as Black, Korean, Latino, White, etc.² While it is widely FN:2 agreed that racial categorization played a crucial role in past racial oppression, there remains disagreement among philosophers and social theorists about the ideal role for racial categorization in future endeavors. At one extreme of this disagreement are short-term eliminativist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 99 publications
0
17
0
Order By: Relevance
“…In addition, studies have repeatedly found that individuals can harbor implicit racial biases that contradict their explicitly held racial attitudes of, for instance, tolerance and racial equality, or their sincerely professed egalitarian ideals. Moreover, those implicit racial biases have been shown to influence judgment and behavior in a number of ways, both in controlled experimental settings, and, only slightly more speculatively, in real‐world situations (for recent overviews of experimental work see Lane, Banaji, Nosek, and Greenwald 2007, Greenwald, Poehlman, Uhlmann, and Banaji 2009; for examples of implicit biases' likely influence on real‐world settings see Bertrand and Mullainathan 2003, Sabin, Nosek, Greenwald, and Rivara 2008, Price and Wolfers forthcoming; for more discussion see Kelly, Machery, and Mallon 2010). Returning to the contact hypothesis, Shook and Fazio (2008) provide experimental evidence that, in addition to reducing explicit racism, contact also reduces implicit biases in advantaged and in disadvantaged racial groups 8 .…”
Section: The Contact Hypothesismentioning
confidence: 99%
“…In addition, studies have repeatedly found that individuals can harbor implicit racial biases that contradict their explicitly held racial attitudes of, for instance, tolerance and racial equality, or their sincerely professed egalitarian ideals. Moreover, those implicit racial biases have been shown to influence judgment and behavior in a number of ways, both in controlled experimental settings, and, only slightly more speculatively, in real‐world situations (for recent overviews of experimental work see Lane, Banaji, Nosek, and Greenwald 2007, Greenwald, Poehlman, Uhlmann, and Banaji 2009; for examples of implicit biases' likely influence on real‐world settings see Bertrand and Mullainathan 2003, Sabin, Nosek, Greenwald, and Rivara 2008, Price and Wolfers forthcoming; for more discussion see Kelly, Machery, and Mallon 2010). Returning to the contact hypothesis, Shook and Fazio (2008) provide experimental evidence that, in addition to reducing explicit racism, contact also reduces implicit biases in advantaged and in disadvantaged racial groups 8 .…”
Section: The Contact Hypothesismentioning
confidence: 99%
“…In the United States this constructionist stance stems at least in part from what SC scholars perceive as an overemphasis on psychological explanations during the nineteen-fifties and nineteen-sixties (for this retreat from psychological and toward structural accounts of racialism see Jackson 1990;Steinberg 1995Steinberg , 2007). CEP's defenders argue that these concerns are misplaced and that their psychological approach is a useful and necessary supplement to constructionist accounts Faucher 2005a, Mallon andStitch 2000) and that a politically powerful antiracist agenda would be enhanced by recognizing the psychology behind racialism (Kelly, Machery and Mallon 2010;Machery, Faucher and Kelly 2010;Kelly, Faucher and Machery 2010;Mallon and Kelly 2012). …”
Section: Cep and The Cognitive Mechanism Underlying Racialismmentioning
confidence: 99%
“…To make such an argument against the race concept in particular, one has to make the argument that racial identitarianism is particularly dangerous, as compared to other forms of social identity, and is so much so to overcome the moral problem with e.g., ethnocide. We will consider a major justification, expressed by racial eliminativists (Kelly, Machery, and Mallon, 2010). It is argued that racial identity and association is particularly invidious because, first, historically biological racial-based associationsas opposed to family, political, cultural, and religious-based oneshave been excessively destructive and because, second, contemporaneously they still are.…”
Section: Vi-d the Moral Critiques: Arguments Based On Racial Classifmentioning
confidence: 99%